√x2 + 1 + √x2 – 2x + 3 = 3
│ x-4 │ - │ 2–0,5x│ ≤ 3
│5- x2-6 │= x2-5x-6
x2-2x+3 : x2-4x+3 > -2
I'm so fail at math soo..would someone please help me ?
For the first one, do you mean $\displaystyle \sqrt{x^2}$?
You need to get rid of the mods here. You can get rid of it by establishing case analysis.│ x-4 │ - │ 2–0,5x│ ≤ 3
$\displaystyle x-4-(2-0.5x) \leq 3$
$\displaystyle 4-x-(2-0.5x) \leq 3$
$\displaystyle x-4-(0.5x-2) \leq 3$
$\displaystyle 4-x-(0.5x-2) \leq 3$
The other one can be done in a similar way.